(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Liver function tests (LFTs) are a critical part of pediatric diagnostic workups for assessing liver health and identifying liver diseases. These tests measure various enzymes, proteins, and substances produced by or processed in the liver, offering insight into liver function, damage, and disease progression. This article reviews the importance of liver function tests in children, including common markers such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT), bilirubin, and albumin. The article also explores how these tests aid in the diagnosis of pediatric liver diseases, such as hepatitis, biliary atresia, cirrhosis, and metabolic liver disorders.